"Cognitive PNF" to implement adolescent muscle-tendon flexibility - Siano, F.; Aquino, M.; Fattore, S. (Journal of Human Sport & Exercise, 2021)
The purpose of this research is to evaluate the significance of concept of proprioceptive neuromuscular facilitation "Cognitive PNF" training in increasing muscle-tendon flexibility over the course of 4 weeks (8 training sessions) in a group of 10 participants aged between 13 and 14 years old, comparing it with another group of 10 participants of the same age, subjected instead to 8 sessions of static stretching. The 20 participants underwent a series of entrance tests, in order to identify the level of flexibility and relative joint mobility of the hip, lumbar spine and shoulder joints: Thomas test, hip extension test, lumbar spine flexion, shoulder range test. Subsequently, through the flexibility index, a lack of flexibility in the participants emerged. The statistical model used for both samples is the T-Test for dependent samples. In the control group, the value of the Stat t (-1.17) falls within the acceptance region which is given by the two-tailed critical t (-2.30; 2.30), therefore, the difference between two averages is not significant. In the experimental group, the value of the Stat t (-5.73) falls outside the acceptance region which is given by the two-tailed critical t (-2.26; 2.26), in other words, in the rejection region rejecting the null hypothesis which states that the difference between the two averages is not significant.